A research paper on the local metal industry capability to manufacture the indigenous Escalona_Esma 5.56mm Assault Rifle (EE 5.56mm AR) - Escalona, Herr K. (University of the Philippines Diliman, 2008)
National Self Reliance in defense and economy is a worldwide goal and form part and parcel of National power. To date the Philippines does not have these two main elements of national power. The defense establishment as an organization is one of the many economic opportunity a country has by locally providing for the its defense needs. Recognizing this potential, then President Ferdinand Marcos issues PD 415 otherwise known as the Self Reliant Defense Posture (SRDP) Program of the Philippine Government. The government went into military equipment research and Development activities. Many of them were a success to an extent but most were a failure. These projects engendered in-country production of our defense needs through partnerships with civilian establishments, and helped developed the local defense industry by maximizing the utilization and processing of indigenous materials and production capability of the country. During the last quarter of 2006, in an effort to help this national SRDP Program, a private Research and Development activity was successfully conducted. This group is made up of hobbyists, professionals, advocates, military and civilian leaders, and metal industry players. The project focused on the goal of having national self sufficiency in assault rifle. After a thorough laboratory testing and some field testing, it was recognized that the capital requirement to establish a traditional rifle line manufacturing facility is magnanimous. The group was compelled to find alternative method/s in manufacturing the indigenous rifle within accepted economic parameters with minimum capital. To do so, great historical economic paradigm were studied to set a benchmark in the production of the EE5.56mmAR. Adam Smith of the late 19th century, Japan's Economic Miracle of the last quarter of the 20th century, and the most recent, that of China's double digit economic growth mainly thru its manufacturing activities. Being a third world country, the country has a very limited financial capital to invest heavily into this indigenous rifle design. Moreover, being a archipelagic in territory, manufacturing activities are localized within the limitations of transportation. Emulating some of the good points of economies cited above and localizing the situation, the approach deemed appropriate for this national goal is that to consider greatly Michael Porter's Diamond of advantage paradigm. He conducted research on industry cluster and developed the Diamond of Advantage, Figure 14, a model that offers insights into industry clusters and competitiveness. Porter contends that nations develop a competitive advantage based on their firms' ability to continually innovate, and that economic vitality is a direct product of the competitiveness of local industries.